The use of lumbar epidural injection of platelet lysate for treatment of radicular pain. (December 2017) - Centeno, Christopher; Markle, Jason; Dodson, Ehren; Stemper, Ian; Hyzy, Matthew; Williams, Christopher; Freeman, Michael
Abstract Background Epidural steroid injections (ESI) are the most common pain management procedure performed in the US, however evidence of efficacy is limited. In addition, there is early evidence that the high dose of corticosteroids used can have systemic side effects. We describe the results of a case series evaluating the use of platelet lysate (PL) epidural injections for the treatment of lumbar radicular pain as an alternative to corticosteroids. Methods Registry data was obtained for patients (N = 470) treated with PL epidural injections presenting with symptoms of lumbar radicular pain and MRI findings that were consistent with symptoms. Collected outcomes included numeric pain score (NPS), functional rating index (FRI), and a modified single assessment numeric evaluation (SANE) rating. Results Patients treated with PL epidurals reported significantly lower (p < .0001) NPS and FRI change scores at all time points compared to baseline. Post-treatment FRI change score means exceeded the minimal clinically important difference beyond 1 month. Average modified SANE ratings showed 49.7% improvement at 24 months post-treatment. Twenty-nine (6.3%) patients reported mild adverse events related to treatment. Conclusion Patients treated with PL epidurals reported significant improvements in pain, exceeded the minimal clinically important difference (MCID) for FRI, and reported subjective improvement through 2-year follow-up. PL may be a promising substitute for corticosteroid.